Integrative chemogenomic analysis identifies small molecules that partially rescue ΔF508‐CFTR for cystic fibrosis - Rachel A. Hodos; Matthew D. Strub; Shyam Ramachandran; Ella A. Meleshkevitch; Dmitri Y. Boudko; Robert J. Bridges; Joel T. Dudley; Paul B. McCray Jr (Wiley, 2021)
Abstract Rare diseases affect 10% of the first‐world population, yet over 95% lack even a single pharmaceutical treatment. In the present age of information, we need ways to leverage our vast data and knowledge to streamline therapeutic development and lessen this gap. Here, we develop and implement an innovative informatic approach to identify therapeutic molecules, using the Connectivity Map and LINCS L1000 databases and disease‐associated transcriptional signatures and pathways. We apply this to cystic fibrosis (CF), the most common genetic disease in people of northern European ancestry leading to chronic lung disease and reduced lifespan. We selected and tested 120 small molecules in a CF cell line, finding 8 with activity, and confirmed 3 in primary CF airway epithelia. Although chemically diverse, the transcriptional profiles of the hits suggest a common mechanism associated with the unfolded protein response and/or TNFα signaling. This study highlights the power of informatics to help identify new therapies and reveal mechanistic insights while moving beyond target‐centric drug discovery.